The History of Sámi Reindeer Husbandry in Greenland and the Transfer of Traditional Knowledge from Sámi Herders to Greenlandic Apprentices - Gaup, Lena Susanne Kvernmo (UiT Norges arktiske universitet, 2019)
Danish authorities introduced reindeer husbandry to Greenland in 1952 when three hundred domesticated reindeer where purchased from a reindeer pastoral district or siida in Kárášjohka and transported to Greenland by boat to the Nuuk fjord. By introducing semi-domesticated reindeer to Greenland, the Danish state intended to establish an abundant new industry and occupation for people, as well as wanting a steady meat supply for Greenland. Behind the decision was the notion of introducing a more ‘civilized’ industry to Greenland, as part of the Danish state’s colonial past. The plan was that the herd would first be owned by the Danish state but would eventually be privatized and run by native Greenlanders. Sámi herders where employed for their expertise on reindeer husbandry to work with the herd, and employed as trainers for the Greenlandic apprentices because of their traditional knowledge and herding techniques in Sámi reindeer husbandry. The Sámi herders were an active part of Greenlandic reindeer husbandry between 1952-1978. Between 1952–1973 the reindeer husbandry at Itinnera in the Nuuk fjord was managed by the Danish authorities. In 1978, the reindeer husbandry in the Nuuk fjord was taken over by the residents of the Kapisillit village and run as a local co-operative until 1998 when the herd was sold to the Nuuk Municipality. This ended reindeer husbandry in the Nuuk region that was also heavily overgrazed. Despite the fact that the reindeer adapted well to Greenland, the animals were in good condition, the herd grew steadily with a peak in 1968-69, and the Sámi herders partly transferred their traditional reindeer herding knowledge to Greenlandic apprentices, the reindeer husbandry did not succeed as the Danish authorities had originally intended. In this thesis, I discuss why reindeer husbandry failed at becoming an abundant and sustainable industry in Greenland. While the failure is often explained with reference to the differences in the hunting culture of the Greenlanders, compared to traditions of ...